Promotional effect of WOx in Pt-WOx/AlPO4-5 catalyzed deoxygenation of fatty acids - Janampelli, Sagar; Darbha, Srinivas (ChemistrySelect, 2017)
WOx promoted Pt/AlPO4-5 catalysts with varying Pt and W contents were prepared by wet-impregnation method and characterized. Catalysts with Pt to W weight ratio of 1: 2 exhibited higher catalytic performance than the other compositions in deoxygenation of oleic acid (OA). WOx enhanced significantly the catalytic activity of Pt and enabled quantitative conversion of OA to linear alkanes (predominantly C-18/C-17) at a temperature as low as 280 degrees C. It changed the reaction pathway from decarbonylation/ decarboxylation (DCO for Pt/AlPO4-5) to hydrodeoxygenation (HDO for Pt-WOx/AlPO4-5). It affected the particle size and redox behaviour of Pt. The enhanced H-spill over (by 14.8%) and presence of strong acid sites (300 - 500 degrees C) are the cause for the high activity of Pt-WOx/AlPO4-5 catalysts even at lower temperatures. Partially reduced WOx activates OA and leads to the HDO product (C-18). In the absence of WOx, Lewis acid sites of the support activate OA through the C=O group and Pt facilitates C-C cleavage and formation of DCO product (C-17).
Keywords: biofuels; Deoxygenation; Fatty acids; Green Diesel; Hydrocarbons

Selective and reusable Pt-WO x /Al 2 O 3 catalyst for deoxygenation of fatty acids and their esters to diesel-range hydrocarbons - Janampelli, Sagar; Srinivas, Darbha (Catalysis Today, 2017)
Tungsten oxide promoted platinum catalysts (Pt-WOx/Al2O3) of varying composition were prepared by wet impregnation method and reduced in hydrogen atmosphere. X-ray powder diffraction and photoelectron spectroscopy revealed that Pt is completely reduced to metallic state while tungsten is in +6 and +5 oxidation state. Pt crystallite and particle sizes increased (from 1.2 to 1.4 nm and 2.5 to 3 nm, respectively) in presence of WOx (CO-chemisorption and transmission electron microscopy). Tungsten addition augmented strong acid sites. It enhanced significantly the catalytic activity of Pt/Al2O3 in deoxygenation of fatty acids and their methyl esters. Tungsten altered the reaction pathway from decarbonylation/decarboxylation to hydrodeoxygenation. A catalyst with 4 wt% Pt and 8 wt% W exhibited high catalytic performance. Complete conversion of oleic acid and octadecane product selectivity in the range 67.1 − 80.8% was obtained. Pt-WOx/Al2O3 is a stable and reusable fatty acid deoxygenation catalyst.
Keywords: biofuels; Deoxygenation; Diesel-range hydrocarbons; Fatty acids; Pt catalyst

Effect of support on the catalytic activity of WOx promoted Pt in green diesel production - Janampelli, Sagar; Darbha, Srinivas (Molecular Catalysis, 2018)
Platinum and WOx-promoted platinum supported on SiO2-Al2O3, Al2O3, AlPO4-5 and ZrO2 catalysts were prepared by wet impregnation method and investigated for deoxygenation of oleic acid (OA, a representative fatty acid) producing diesel-range hydrocarbons. Support and WOx influenced the textural, electronic and catalytic properties of Pt. WOx promoted the deoxygenation activity through hydrodeoxygenation pathway. Structure-activity correlations revealed that metallicity of Pt and acidity of the catalyst are crucial in determining the catalytic performance and product selectivity. Among the catalysts tested, 4Pt-8WO(x)/ZrO2, having adequate metal dispersion and electron rich Pt (desired for hydrogen splitting), reduced WOx species (W5+;-desired for OA activation) and less amount of strong acid sites (desired to avoid hydrocracking) showed highest catalytic deoxygenation performance (OA conversion = 100 mol% and C18 hydrocarbon selectivity = 89.4% at 260 degrees C and 20 bar H-2 pressure). The study reveals that support plays a crucial role in determining the catalytic performance of platinum. (C) 2017 Elsevier B.V. All rights reserved.

Metal oxide-promoted hydrodeoxygenation activity of platinum in pt-mox/al2o3 catalysts for green diesel production - Janampelli, Sagar; Darbha, Srinivas (Energy & Fuels, 2018)
Catalytic deoxygenation of fatty acids into renewable hydrocarbons (green diesel) was investigated over 4Pt-8MO(x)/Al2O3 (M = Mo, Re, W, and Sn) catalysts prepared by the wet impregnation method. Platinum deposited on MOx-modified gamma-Al2O3 showed higher catalytic hydrodeoxygenation activity than that of the "neat" Pt/Al2O3 catalyst. The promotional effect of metal oxides (MOx) decreased in the following order: MoOx > ReOx > WOx > SnOx. Characterization studies revealed that metal oxides affect the textural and electronic properties of Pt. Supported Pt facilitated the reduction of these metal oxides. Synergy and electronic contact between Pt and MOx determined the catalytic deoxygenation performance. Fatty acid conversion increased with increasing metallic nature (decreasing binding energy) of Pt. Hydrodeoxygenation product selectivity correlated with the extent of metal oxide reduction. Among the catalysts, 4Pt-8MoO(x)/Al2O3 had the optimum dispersion, electron-rich Pt, and reduced Mo5+ species, enabling quantitative conversion of oleic acid with 93.5% octadecane selectivity at a temperature as low as 220 degrees C and 20 bar hydrogen pressure. Metal oxide switched the mechanism of deoxygenation from decarbonylation/decarboxylation to hydrodeoxygenation. Fatty acids, methyl oleate, and vegetable oil were deoxygenated with equal efficiency over this catalyst. Catalysts were reusable in recycling studies only at higher temperature (320 degrees C) and not at lower temperature (260 degrees C), perhaps due to strong sticking of reactant molecules at lower temperature on the catalyst surface than at higher temperature.

Dry reforming of methane in DBD plasma over Ni-based catalysts: influence of process conditions and support on performance and durability - Ray, Debjyoti; Nepak, Devadutta; Janampelli, Sagar; Goshal, Partha; Subrahmanyam, Ch (Energy Technology, 2019)
The conversion of greenhouse gases, H-2 and CO selectivity, H-2/CO ratio, and carbon formation in the dry reforming reaction over Ni-supported ZSM-5, Al2O3, and TiO2 are tested under thermal, plasma, and plasma-thermal conditions. It is observed that the dielectric nature, specific surface area, and acid-base properties of the support influence the performance during the DRM reaction. Typical results indicate that the best activity and syngas yield are achieved with 15Ni/Al2O3 under plasma conditions, possibly due to the high dielectric constant and surface area of Al2O3 and nanosize of Ni. In the thermal condition, the highest conversion of 73% and 68% for CH4 and CO2, respectively, is achieved over 15Ni/ZSM-5 at 500 degrees C. Plasma-assisted thermal conditions provide the highest conversion due to the activation of reactants and their partial conversion in the plasma zone before entering into the catalytic zone. The plasma-assisted thermocatalytic conversions of CH4 and CO2 reach the best values of 76% and 71%, respectively, on 15Ni/ZSM-5. Under the same conditions, 68% and 65% conversion of CH4 and CO2, respectively, is achieved with 15Ni/Al2O3 where the selectivity for H-2 and CO is 45% and 58%, respectively.
Keywords: DBD plasma; Dry reforming; reaction conditions; supported catalysts; Syngas

Highly efficient Pt-MoOx/ZrO2 catalyst for green diesel production - Janampelli, Sagar; Darbha, Srinivas (Catalysis Communications, 2019)
Bimetallic Pt-MoOx supported on ZrO2 exhibits higher catalytic activity than known catalysts for converting fatty acids into green diesel at as low as 200 degrees C. A change in selectivity from decarboxylation/decarbonylation to hydrodeoxygenation and enhancement in the deoxygenation activity of Pt were observed when MoOx was also present in the catalyst composition. In X-ray photoelectron spectra, Pt 4f lines of 4Pt-8MoO(x)/ZrO2 occurred at lower binding energies than those for 4Pt/ZrO2. Part of Mo was reduced from +6 to +5 oxidation state in the presence of Pt. There seems to exist some electronic interaction between the support and metal, making 4Pt-8MoO(x)/ZrO2 a highly efficient and selective deoxygenation catalyst.
Keywords: Bimetallic catalyst; Biofuel; Deoxygenation of fatty acids; Green Diesel; Hydrocarbons; Supported platinum catalyst

Hydrodeoxygenation of vegetable oils and fatty acids over different group VIII metal catalysts for producing biofuels - Janampelli, Sagar; Darbha, Srinivas (Catalysis Surveys From Asia, 2019)
Energy security and environment protection are two important aspects of sustainable development. Biofuels are renewable and carbon neutral. They are suitable replacement for conventional fossil derived transport fuels. Their use leads to sustainable development. Among several technological options, catalytic hydrodeoxygenation of vegetable oils leading to diesel-range hydrocarbons is the most attractive approach for producing biofuels. The green diesel, thus produced, could be blended with petro-diesel or used as standalone fuel in the conventional diesel engines. Our research group has been active in developing efficient solid catalysts for hydroprocessing of vegetable oils. This account presents some of our efforts using supported group VIII metals and the importance of electronic contact between metal and support on the catalytic activity and hydrodeoxygenation selectivity in hydroprocessing of vegetable oils.
Keywords: biofuels; Catalysis over group VIII metals; Deoxygenation; Hydroprocessing; Renewable diesel

Selective, bifunctional Cu-WOx/Al2O3 catalyst for hydrodeoxygenation of fatty acids - Janampelli, Sagar; Sethia, Govind; Darbha, Srinivas (Catalysis Science & Technology, 2020)
Selective hydrodeoxygenation of oleic acid (OA; in a batch reactor, at 300 degrees C, 30 bar H-2 pressure, reaction time of 1 h and reactant-to-catalyst weight ratio of 2 g OA/0.2 g) forming n-octadecane in yields as high as 93% over a non-noble metal, sulfur-free, bimetallic Cu-WOx/Al2O3 catalyst is reported for the first time. Several Cu-WOx/Al2O3 compositions were prepared by a sequential wet-impregnation method and evaluated. A catalyst with 10 wt% Cu and 4 wt% W enabled the highest activity and selectivity. Upon adding WOx, the amount of moderate and strong acid sites increased and more Cu in the catalyst was in reduced electron-rich metallic (Cu-0) state. The crystallite size and dispersion of Cu were little affected. WOx promoted the fatty acid hydrodeoxygenation activity of Cu. While a monometallic Cu catalyst (10Cu/Al2O3) yielded n-octadecane and n-heptadecane along with high amounts of intermediate octadecanol and octadecanal products, the bimetallic catalyst (10Cu-4WO(x)/Al2O3) gave mainly n-octadecane. Acidity and the high amount of reduced Cu-0 species are responsible for the high catalytic hydrodeoxygenation performance of this bimetallic catalyst.

Selective deoxygenation of fatty acids to fuel-range hydrocarbons over Pt-MOx/ZrO2 (M = Mo and W) catalysts - Janampelli, Sagar; Darbha, Srinivas (Catalysis Today, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">A comparative catalytic activity study of Pt-MoO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and Pt-WO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> for deoxygenation of oleic acid (OA) forming fuel-range, linear hydrocarbons is reported. These catalysts (with 4 wt% Pt and 8 wt% Mo or W) were prepared by a sequential wet-impregnation method and characterized for the structural and electronic properties. Pt-MoO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> showed higher catalytic activity than Pt-WO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">x<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. Hydrodeoxygenation was the selective pathway over these bifunctional catalysts yielding n-octadecane. High conversion of OA was achieved at 200 °C itself. On the contrary, monometallic Pt/ZrO<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> was weakly active. It was selective mainly toward decarboxylation/decarbonylation producing n-heptadecane. Higher amounts of Pt and metal oxide in reduced forms are responsible for the high hydrodeoxygenation activity and selectivity of these reusable, bimetallic catalysts.